The influence of patient characteristics on acrylic-based resilient denture liners embedded in maxillary complete dentures. Issue 3 (July 2016) - Ogawa, Akina; Kimoto, Suguru; Saeki, Hiroyuki; Ono, Masanori; Furuse, Nobuhiko; Kawai, Yasuhiko
Abstract: Purpose: A major complication associated with the use of resilient denture liners (RDLs) is a change in hardness over time. In vivo studies on the deterioration of RDLs over time are needed. We aimed to investigate the influence of patient characteristics on the hardness of acrylic-based RDLs (ARDLs) embedded in complete maxillary dentures. We hypothesized that 1 month after application of the ARDLs, the hardness would be influenced by age, saliva condition, occlusal force, smoking, drinking, denture wearing during sleeping, denture cleanser usage, and denture type. Methods: Thirty complete maxillary denture wearers were recruited after obtaining informed consent. One investigator measured the Shore D hardness of the commercially available ARDLs, Soften (SFT), FD Soft (FDS), and Bio Liner (BIO) using a Vesmeter ® . The salivary flow rates and pH values and the occlusal force were measured for all patients before initiation of the study. T -tests and Pearson's correlation coefficients were used for the statistical analyses. A p -value of <0.05 was considered statistically significant. Results: Smoking, wearing dentures while sleeping, use of denture cleansers, and denture type were associated with an increase in the hardness of the RDLs. The resting saliva pH only influenced the hardness of the SFT ARDLs. Conclusions: Smoking, denture wearing while sleeping, denture cleanser usage, denture type, and resting saliva pH are important predictors of the deterioration of ARDLs over time.